2011
DOI: 10.1068/i0459aap
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Transparency

Abstract: Artists throughout the ages have discovered a number of techniques to depict transparency. With only a few exceptions, these techniques follow closely the properties of physical transparency. The two best known properties are X-junctions and the luminance relations described by Metelli. X-junctions are seen where the contours of a transparent material cross contours of the surface behind; Metelli's constraints on the luminance relations between the direct and filtered portions of the surface specify a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…The low rating score for the static image condition suggests that a static deformation image cannot provide a clear impression of transparent liquid, in agreement with a previously reported suggestion (5). A low score for the no-motion condition suggests that multiple deformation images cannot provide a clear impression of transparent liquid either, and that low-level motion signals detected by low-level motion detectors play a critical role in the perception of transparent liquid.…”
Section: Importance Of Dynamic Image Deformation In Seeing a Transparentsupporting
confidence: 78%
See 1 more Smart Citation
“…The low rating score for the static image condition suggests that a static deformation image cannot provide a clear impression of transparent liquid, in agreement with a previously reported suggestion (5). A low score for the no-motion condition suggests that multiple deformation images cannot provide a clear impression of transparent liquid either, and that low-level motion signals detected by low-level motion detectors play a critical role in the perception of transparent liquid.…”
Section: Importance Of Dynamic Image Deformation In Seeing a Transparentsupporting
confidence: 78%
“…When a transparent layer has a refractive index >1, the background image optically deforms in accordance with the 3D shape of the layer surface. The image deformation due to refraction by itself is considered an ineffective cue to the perception of a transparent layer (5), although the magnitude of the deformation could be a cue to the perception of the thickness of a transparent layer (6). Previous studies have examined the effect of the deformation cue only in static images, however.…”
mentioning
confidence: 92%
“…In the study The Art of Transparency [51], Sayim and Cavanagh describe experiments by Metelli that have shown how these crossings or X-junctions are critical cues for the successful depiction of transparency. This raises the question as to why line drawings work so well for our visual brain?…”
Section: Boundaries As Linesmentioning
confidence: 99%
“…Such image deformations, generated by a transparent material, can be a cue that causes the visual system to recognize a transparent layer. Although an observer can easily perceive image deformation due to refraction in a still image, it has been shown that static image deformations do not serve as a strong cue to perceptual transparency, as shown in figures 1 and 12 of Sayim and Cavanagh (2011). Some previous studies have reported that static image deformations produce only weak impressions of water and hot air (Kawabe & Kogovšek, 2017;Kawabe, Maruya, & Nishida, 2015).…”
Section: Introductionmentioning
confidence: 96%